Nationalism and self-government in Rhodesian detention: Gonakudzingwa, 1964-1974 - Alexander, J (Routledge, 2011)
Political prisoners have commonly resisted the terms of their imprisonment. Under certain circumstances, they have also sought to displace the state's authority with their own institutions of government. These efforts provide a unique window onto political ideas and ‘languages of stateness’, as well as the effects of particular conditions of confinement. ZAPU detainees' practices in the remote outpost of Gonakudzingwa revealed a commitment to a model of bureaucratic power that drew on the Rhodesian state while also offering a critique thereof. Detainees constructed a hierarchy of rule-bound and specialised committees that closely regulated daily life; they imagined an inclusive nationalist mythology, and they promoted civility and restraint. Detainee self-government could not contain all divisions and disputes, but it did offer an alternative vision of nationalism and authority that stood in stark contrast to the practices of nationalists and guerrillas in exile and in the war zones of Rhodesia.